Response of laminated float glass to 9 mm projectile impact. (2022) - Sovják, Radoslav; Konrád, Petr; Hála, Petr; Zatloukal, Jan; Schmidt, Jaroslav; Zemanová, Alena; Janda, Tomáš; Zeman, Jan; Šejnoha, Michal
Abstract: This paper presents an experimental study on the performance of laminated float glass plates against high-velocity projectile impact. Two configurations of the specimen's layers were used, 5 layers (3 glass and 2 polymer interlayers) and 7 layers (4 glass and 3 polymer interlayers). The specimens were suspended on steel ropes for stress-free boundary conditions. The projectile was a standard in-service 9 mm Luger fired from a distance of 20 m. The results showed that both layer configurations are more than capable of stopping the projectile. However, only the higher layer count was able to stop the formation of significant damage to the backside of the specimen, from which a certain amount of harmful debris could have been released. The higher layer count also prevented the formation of radial cracks.